Rovibrational Interaction and Vibrational Constants of the Symmetric Top Molecule 14NF3 - Hamid Najib (The Scientific World Journal)
Several accurate experimental values of the and rotation-vibration interaction parameters and , , and vibrational constants have been extracted from the most recent high-resolution Fourier transform infrared, millimeter wave, and centimeter wave investigations in the spectra of the oblate symmetric top molecule 14NF3. The band-centres used are those of the four fundamental, the overtones, the combination, and hot bands identified in the region between 400 cm−1 and 2000 cm−1. Comparison of our constants with the ones measured previously, by infrared spectroscopy at low resolution, reveals orders of magnitude higher accuracy of the new values. The agreement between our values and those determined by ab initio calculations employing the TZ2Pf basis is excellent.